Role of Sawdust in the Removal of Iron from Aqueous Solution - H.B. Senin; O. Subhi; R. Rosliza; N. Kancono; M.S. Azhar; S. Hasiah; W.B. Wan Nik (ASEAN Journal on Science and Technology for Development, 2006)
Sawdust, inexpensive material has been utilized as an absorbent for the removal of iron from aqueous solution for their safe disposal. The adsorption experiments of untreated sawdust (SD) and treated sawdust (SDC) have been carried out at room temperature using the batch test. The Langmuir and Freundlich isotherms were used to observe sorption phenomena of sawdust in the removal of iron. The results indicate that the sawdust was capable in removing iron in aqueous solution. The results have shown that the Langmuir isotherm was found well fitted into the experimental data as compared to the Freundlich isotherm. It was found that, chemisorptions and physisorption were the prime mechanism for the process of adsorption to occur between the sawdust and iron. The results also proved that the acid sulphuric treated sawdust is much better than that of untreated sawdust as an adsorbent for iron.